Effects of selected economic growth indicators on the financial performance of Sacco societies in Kenya - Nyandika, Julius Nyaata; Muturi, Willy; Mogwambo, Vitalis A. (ijssit.com, 2016)
The purpose of this study was therefore to assess the effects of economic growth indicators on the financial performance of the SACCO’s in Kenya taking Kenya Achievas Sacco Society limited as a case study. Four theories that were adopted for the research were; Irvin Fisher’s theory on real interest rates, Bentil Ohlin’s loanable Funds Theory, John Maynard Keynes’ classical theory of interest rate and Keynesian Theory of inflation. The research found out that there was strong positive relationship between economic growth indictors with financial performance of SACCOs in Kenya. It was also discovered that high inflation rates and high interest rates had strong effect on financial performance of SACCOs in Kenya since they affected the members savings and borrowing for investments from SACCOs.
Keywords: Effects; Growth Indicators; Financial Performance; Savings and Credit Co-operative (SACCO)